ANALISIS FAKTOR INTERNAL DAN EKSTERNAL YANG MEMPENGARUHI KINERJA KEUANGAN BANK PEMBANGUNAN DAERAH DI INDONESIA PERIODE 2010-2013 - Nyoman Kesumayuda, I B; Suyana Utama, Made; Purbadharmaja, I B P (Buletin Studi Ekonomi; VOL.21.NO.1.FEBRUARI.2016 (PP 1-114), 2016)
Abstract : Analysis of Internal and External Factors Influencing Financial Performance IndonesiaRegional Development Bank Period From 2010-2013. The financial performance of banks is a picture ofthe financial condition of the bank as a collector and distributor of funds in certain periods. Rise and fallof the resulting financial performance, may be affected by several factors both inside and outside thebank. This study was aimed to investigate the influence of internal factors, external factors, and riskfactors on the financial performance of BPD in Indonesia. Data used in the form of secondary data.Population as well as samples in this study were 26 BPD in Indonesia period 2010-2013, using SEM-PLSanalysis techniques. In accordance with the results of the data analysis was concluded that the internalfactors have a significant positive effect on financial performance and significant negative effect on therisk factors, external factors and risk factors have a significant negative effect on the financial performance,external factors have a significant positive effect on the risk factors of banks, and there is the indirecteffect of internal factors and external factors on the bank’s financial performance BPD in Indonesia,which is mediated by the bank’s risk factors.   Keywords: bank’s internal factors, bank’s external factors, bank’s risk factors and financial performance.
Keywords: bank’s internal factors, bank’s external factors, bank’s risk factors and financial performance.